The Phatic Category in Toraja Dialect Kendek on Buying and Selling Transactions in Ge'tengan Market - Milka, Milka; Simega, Berthin; Mangera, Elisabet (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe (1) the form of phatic categories of the Toraja language in the Mengkendek dialect, (2) to describe the functions of the phatic categories of the Mengkendek dialect in buying and selling transactions at the Ge'tengan market. This research uses a qualitative descriptive research type. The techniques used in data collection are note-taking and recording techniques. The data in this study are the utterances of the Toraja people. The data source in this study is the Toraja people who use the Mengkendek dialect in buying and selling transactions at the Ge'tengan market. The benefits of this research can be used as teaching material in local content subjects at the elementary school level and can be used as an alternative material in the use of Toraja language for the Toraja people. In this study using a hermeneutic approach. The hermeneutic approach is used to complete the data found in the field. The tool in this research is the researcher himself. Data analysis techniques were carried out by (1) transcribing the recorded and observed data, (2) identifying data in the form of phatic categories found in buying and selling transactions at the Ge'tengan market, (3) grouping recorded data based on phatic category forms, (4) violation of the form of phatic categories used by the Toraja people in carrying out buying and selling transactions at the Ge'tengan market, (5) conclusion. The results of the study include the form of phatic categories including (a) particles in the form of le, oh, (b) words in the form of iyo, mi, na, (c) phrases in the form of kurre sumanga, ta lendu' opa, maballo liu, lendu maballona, phatic function includes (a) starting communication between sellers and buyers (b) starting conversations between sellers and buyers, (c) stopping communication, and (d) arranging communication. AbstrakPenelitian ini bertujuan untuk mendeskripsikan (1) bentuk kategori fatis bahasa Toraja dialek Mengkendek, (2) mendeskripsikan fungsi kategori fatis dialek Mengkendek dalam transaksi jual beli di pasar Ge’tengan. Penelitian ini menggunakan jenis penelitian deskriptif kualitatif. Teknik yang digunakan dalam pengumpulan data adalah teknik catat dan rekaman. Data dalam penelitian ini berupa tuturan masyarakat Toraja. Sumber data dalam penelitian ini adalah masyarakat Toraja yang menggunakan dialek Mengkendek dalam transaksi jual beli di pasar Ge’tengan. Manfaat penelitian ini dapat dijadikan sebagai bahan ajar dalam mata pelajaran muatan lokal di tingkat sekolah dasar dan dapat dijadikan sebagai bahan alternatif dalam penggunaan bahasa Toraja bagi masyarakat Toraja. Dalam penelitian ini menggunakan pendekatan hermeneutika. Pendekatan hermeneutika digunakan untuk menafsirkan data yang ditemukan di lapangan. Instrumen dalam penelitian ini adalah peneliti sendiri. Teknik analisis data dilakukan dengan (1) mentranskripsi  data hasil rekaman  dan simakan, (2) mengidentifikasi data berupa kategori fatis yang ditemukan dalam transaksi jual-beli di pasar Ge’tengan, (3) mengelompokkan data hasil rekaman berdasarkan bentuk kategori fatis, (4) menafsirkan bentuk kategori fatis yang digunakan masyarakat Toraja dalam melaksanakan transaksi jual beli di pasar Ge’tengan,  (5) penyimpulan. Hasil penelitian  meliputi bentuk kategori phatic meliputi (a) partikel berupa le, oh,  (b) kata berupa iyo, mi, na, (c) frasa berupa kurre sumanga, ta lendu' opa, maballo liu, lendu maballona,  Fungsi fatis meliputi (a) memulai komunikasi antara penjual-pembeli (b) memulai pembicaraan antara penjual-pembeli, (c) menghentikan komunikasi, dan (d) merangkai komunikasi